Risiko dan Kinerja Portofolio pada Berbagai Tingkat Diversifikasi Saham Berkapitalisasi Besar di Indonesia - Khairul Alim; Corry Sormin (CV. ITTC INDONESIA, 2026)
Portfolio diversification is a widely used investment strategy to reduce risk by allocating funds across different assets. However, the effectiveness of increasing the number of stocks in reducing risk while improving portfolio performance remains a subject of debate, particularly for large-cap stocks in the Indonesian capital market. This study aims to analyze the effect of increasing the number of stocks on portfolio risk and performance among large-cap stocks listed on the Indonesia Stock Exchange during the 2020–2024 period. This study employed a quantitative approach with a comparative descriptive research design. The population comprised all stocks listed on the Indonesia Stock Exchange, while the sample consisted of 15 large-cap stocks selected using purposive sampling. Monthly closing price data were obtained from Yahoo Finance and the Indonesia Stock Exchange. Portfolios were constructed using the equal-weighting method and grouped into five portfolios consisting of 3, 6, 9, 12, and 15 stocks. Data were analyzed using portfolio return, standard deviation, and the Sharpe Ratio. The results indicate that portfolio returns increased from 0.234% to 0.674% as the number of stocks in the portfolio increased. However, portfolio risk also rose from 4.208% to 5.400%, indicating that adding more stocks does not necessarily reduce portfolio risk. Nevertheless, the Sharpe Ratio improved from −0.039 to 0.052, suggesting an improvement in risk-adjusted portfolio performance. This study concludes that increasing the number of stocks in a portfolio does not always result in lower risk, but it can improve portfolio returns and risk-adjusted performance. These findings provide practical insights for investors in determining an appropriate level of diversification when investing in large-cap stocks listed on the Indonesia Stock Exchange.